HUBUNGAN MANUSIA DAN ETOS KERJA DALAM KOTOWAZA JEPANG - Sri Wahyu Istana Trahutami (Diponegoro University, 2018)
(Title: Human Relationship and Work Ethos in Japanese Kotowaza). Kotowaza ‘proverbs’ are nuggets of traditional wisdom which have been passed down through the ages, can be found in many societies in the world. Proverbs like a guidance for humans to act and behave in their daily lives. We can know how people perceive work through kotowaza. Kotowaza teaching us to work hard, diligent, tenacious and so on. The doctrine of goodness is a guide for the community where the proverbs born.